Health‐related quality of life outcomes after surgical treatment of atypical femur fractures: a multicenter retrospective cohort study - Jonathon Spanyer (Wiley, 2021)
ABSTRACT The objective of this study was to examine the health‐related quality of life (HRQOL) outcomes for surgically‐treated atypical femur fractures (AFFs) compared to typical femoral diaphyseal fractures. Two large trauma center databases were retrospectively queried for surgically‐treated femur fractures. Fractures were grouped into AFFs and compared to a control cohort. Controls for the AFF group included women with diaphyseal fractures without additional AFF characteristics. Patients were contacted for administration of the Short Form‐36v2 Health Survey. Surveys were completed an average of 30.3 months (range, 6–138 months) and 25.5 months (range, 5–77 months) postoperatively for the AFF and non‐AFF groups, respectively. All patients were female, with 46 patients in the AFF and 26 patients in the non‐AFF group. The average age of the AFF group was 70.1 years compared with an average age of 67.4 years in the non‐AFF group (p = 0.287). Over 90% (91.3%) of patients in the AFF group had a history of bisphosphonate use while 26.9% of patients in the non‐AFF group had used bisphosphonates (p < 0.0001). Patients with AFF reported their postoperative physical and mental health to be no different than similarly aged patients with femoral diaphyseal fractures, as measured by the Short Form 36, version 2 (SF‐36v2) Health Survey. These data suggest that mid‐term patient‐reported quality of life outcomes are similar among women who sustain an AFF compared to a cohort of more typical femoral diaphyseal fractures. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC. on behalf of American Society for Bone and Mineral Research.